2018
DOI: 10.1021/acs.jmedchem.8b00760
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacology by Design: A Medicinal Chemist’s Perspective on Multitargeting Compounds

Abstract: Multitargeting compounds comprising activity on more than a single biological target have gained remarkable relevance in drug discovery owing to the complexity of multifactorial diseases such as cancer, inflammation, or the metabolic syndrome. Polypharmacological drug profiles can produce additive or synergistic effects while reducing side effects and significantly contribute to the high therapeutic success of indispensable drugs such as aspirin. While their identification has long been the result of serendipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
334
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(375 citation statements)
references
References 258 publications
(365 reference statements)
1
334
0
2
Order By: Relevance
“…[145] Polypharmacology represents an increasingly recognizeds trategy for the treatment of complex diseases,such as cancer or CNS diseases. [146][147][148][149][150][151] Pochetti et al reported two inhibitors of MMP-8t hat bind to an S1'*p ocket previously unobserved for humann eutrophil collagenase . [152] This extra binding region is formed through the rearrangement of the Tyr227 side chain induced by the inhibitors.…”
Section: Non-zinc-binding Inhibitorsmentioning
confidence: 98%
See 1 more Smart Citation
“…[145] Polypharmacology represents an increasingly recognizeds trategy for the treatment of complex diseases,such as cancer or CNS diseases. [146][147][148][149][150][151] Pochetti et al reported two inhibitors of MMP-8t hat bind to an S1'*p ocket previously unobserved for humann eutrophil collagenase . [152] This extra binding region is formed through the rearrangement of the Tyr227 side chain induced by the inhibitors.…”
Section: Non-zinc-binding Inhibitorsmentioning
confidence: 98%
“…In a similar approach, the group developed a dual inhibitor for the target enzymes MMP‐7 and ‐13 . Polypharmacology represents an increasingly recognized strategy for the treatment of complex diseases, such as cancer or CNS diseases …”
Section: Mmp Inhibitorsmentioning
confidence: 99%
“…The organic phase was evaporated under reduced pressure, and the aqueous phase was 4.1.8. N-(6-Chloro-1,2,3,4-tetrahydroacridin-9-yl)-N'- (9-fluoro-7H-5,6,8,9,10,11hexahydro-5,9:7,11-dimethanobenzo[9]annulen-7-yl)-1, 5- 4.1.9. tert-Butyl (9-fluoro-7H-5,6,8,9,10,11-hexahydro-2-nitro-5,9:7,11dimethanobenzo[9]annulen-7-yl)carbamate (15) To a mixture of amine 14 [59] (496 mg, 1.79 mmol) and 2N NaOH (1.4 mL) in THF 4.1.10. tert-Butyl (2-amino-9-fluoro-7H-5,6,8,9,10,11-hexahydro-5,9:7,11dimethanobenzo[9]annulen-7-yl)carbamate (16) A suspension of the nitro derivative 15 (583 mg, 1.54 mmol) and PtO2 (48 mg, 0.12 mmol) in EtOH (100 mL) was hydrogenated at 1 atm of H2 at room temperature for 4 h. Hz, 1H, 4-H); 13 4.1.11. N-(7-Amino-9-fluoro-7H- 5,6,8,9,10,11-hexahydro-5,9:7,11-…”
Section: -Butanediamine (13a)mentioning
confidence: 99%
“…Multitarget treatments may involve the use of several specific drugs (drug cocktails or fixed-dose combinations) or a single drug with the ability to hit several biological targets (multitarget drugs). Even though the design and development of multitarget drugs can be very challenging [12], it has some clear advantages over multiple-medication therapies, such as simpler dose regimens and improved patient compliance, simpler pharmacokinetics and lack of drug-drug interactions, and simpler clinical development, among others [13,14]. In fact, both strategies are being currently used in AD treatment or pursued in AD drug discovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation